2022
DOI: 10.1155/2022/8336743
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Model of Student Satisfaction in International Student Education Based on Neural Networks

Abstract: Artificial neural network (ANN) theory is a rapidly developing information science around the world. The Back Propagation (BP) network is one of many artificial neural network types. It is a multilayer feedforward network with sophisticated nonlinear mapping capabilities. It is actually a relatively complex and nonlinear comprehensive decision-making problem when taking into account the comprehensive evaluation of test scores based on evaluation indicators that reflect the quality of the test papers. The five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The construction of this model was based on the intelligent analytic method to pragmatic failure in cross-cultural communication. Wang and Gao [23] have suggested that Neural network-based student satisfaction evaluation methodology for overseas students studying abroad. The five primary factors that determine the quality of education services were modeled and analyzed using a neural network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The construction of this model was based on the intelligent analytic method to pragmatic failure in cross-cultural communication. Wang and Gao [23] have suggested that Neural network-based student satisfaction evaluation methodology for overseas students studying abroad. The five primary factors that determine the quality of education services were modeled and analyzed using a neural network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The five factors of the education service quality evaluation model were examined individually, and the problems existing in the education service quality of international students in China were analyzed. The empirical study shows that the overall satisfaction of international students in China with the quality of education services in Guangxi is low, and all the indicators of education level are low [1]. Wenxin Du (2019) explored how to strengthen the education management of international students in China, understand the problems, and put forward targeted countermeasures [2].…”
Section: Literature Reviewmentioning
confidence: 99%